1997
DOI: 10.1364/ao.36.004403
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent optical absorption characteristics of titanium dioxide thin films

Abstract: We used the electron-beam evaporation method in various oxygen partial pressure environments to deposit TiO(2) thin films on various glass substrates at 300 degrees C. We found the threshold oxygen partial pressures above which the film is transparent are different for films on various substrates. Below the threshold oxygen partial pressure, the refractive index and the extinction coefficient of the films varied from substrate to substrate. The films on substrates with higher threshold oxygen partial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…1,2 Cross sections of micrographs from scanning electron microscopy and transmission electron microscopy have provided direct information about the nanostructure of the multilayer systems, although many other techniques have been utilized to characterize films ͑x-ray diffraction, electron diffraction, Auger electron spectroscopy, x-ray fluorescence, etc.͒. It is currently known that most evaporated films are formed by a nanostructure composed of nanometric-size columns, amorphous or crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Cross sections of micrographs from scanning electron microscopy and transmission electron microscopy have provided direct information about the nanostructure of the multilayer systems, although many other techniques have been utilized to characterize films ͑x-ray diffraction, electron diffraction, Auger electron spectroscopy, x-ray fluorescence, etc.͒. It is currently known that most evaporated films are formed by a nanostructure composed of nanometric-size columns, amorphous or crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variety of techniques has been used for the preparation of TiO 2 films [1][2][3][4]. For instance, Bennett et al [5] and Chen et al [6] have reported that the optical properties of the TiO 2 films deposited by electronbeam evaporation, such as refractive index, extinction coefficient and scattering losses, are strongly process-dependent and are especially sensitive to oxygen partial pressure. So, the determination of the oxygen content of TiO 2 films deposited by electron-beam evaporation at different oxygen partial pressures is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Various properties of the extensively studied metal oxide TiO 2 have been of interest, including deposition process control, [1] crystal structure, [2] phase stability, [3±5] optical quality, [6,7] (electro)luminescence, [8] photosensitivity, [9] microhardness, [6] epitaxial growth, [10] permittivity, [11,12] and leakage current. [5,12,13] With reference to factors affecting the physical properties, an interesting aspect in TiO 2 growth has been the stability of various crystallographic phases such as anatase and rutile.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, pure anatase is optically less absorbent than rutile. [7] As a metastable polymorph of TiO 2 , anatase is often first to form at relatively low processing temperatures, especially in fine-grained form. [2,3,14] Possibly the lowest reported in-situ processing temperature of pure rutile has been 300 C in laser ablation, [15] or rutile mixed with anatase in films evaporated at 300 C and above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation